Integrated Assesment of Indian Spices as Immunity Boosters (Global Journal of Medical Research, 2020)
With the outbreak of pandemic immune boosting is very essential for each and every human being. The idea of boosting your immune system is appealing which can only be achieved by intake of essential food ingradients in our daily meals. Functional foods may be designed by supplementation with an active ingredient that is known for its health benefits. The long list of beneficial physiological effects of Indian spices like Turmeric, Ginger, Fennel, Cinnamon suggest that it might be considered as an essential part of human diet and act as potential antioxidant and antiviral agents.
Keywords: immunnity; antiviral; antiinflammatory; antioxident; spices